The influence of communication language on purchase intention in consumer contexts: the mediating effects of presence and arousal - Huang, Wenjun; Leong, Yee Choy; Ismail, Noor Azlin (Springer, 2023)
Panoramic visual, tactile, and auditory interactions have been widely used to create scene-based immersive experiences to enhance consumer experience and stimulate emotional responses, thereby increasing purchase intentions. Guided by scene marketing theory and the archetypal theory of mind-flow experience, this article introduces the concepts of presence and emotional arousal to examine how communication language causes emotional fluctuations in potential consumers, leading to purchase intentions. Therefore, from the interaction experience of “external perception - scene language” and “internal sensing - communication language”, the dual chain of mediation of presence perception and emotional arousal is selected to construct a consumer. The results reveal that the pathway of consumers’ purchase intentions is not always the same in the context of consumer language perception. In addition, the results demonstrate that the vividness and richness of the presentation of scene language in a consumer language perception context have positively influenced the relationship between communication language and presence perception. Compared to the direct effect on purchase intention, communication language tends to have an indirect positive effect on consumers’ purchase intention through the single mediation of presence perception and the chain mediation of emotional arousal. The increasing prevalence of interactive linguistic experiences, where emotional arousal has become an essential trigger for consumers’ purchase intentions, is an important representation of the specificity and complexity of consumer language elements. Thus, this research provides crucial theoretical guidance for the design of immersive experiential marketing and linguistic scenarios.